The role of community of inquiry and self-efficacy on accounting students’ satisfaction in online learning environment - Fachmi Pachlevi Yandra; Badr Alsolami; Ivana Oktarina Sopacua; Wisnu Prajogo (Jurnal Siasat Bisnis, 2021)
The Community of Inquiry (CoI) framework provides a solid guideline for researchers to investigate a quality of online learning. However, there are still very limited studies that explore the pattern of relationships between CoI framework and accounting students’ satisfaction in online learning. In the context of online learning, self-efficacy plays a role to determine the level of students’ confidence to get success in the learning process. Students with a high level of self-efficacy will not perceive a difficult task as an obstacle to be avoided, but rather as a challenge to develop abilities. This research aims to explore the relationship between CoI framework and accounting students’ satisfaction through online learning self-efficacy. Self-administered survey was conducted to 437 accounting students. Hypothesis was tested using SEM-PLS. Results showed that CoI framework were good predictors of accounting students’ satisfaction. Different from most studies, this research found that students were more influenced by social presence instead of teaching presence. Higher educational institutions needed to focus on how to improve social presence in the online learning environment. In addition, higher educational institutions needed to manage students' online learning self-efficacy instead of technology self-efficacy.